Weber and Castoriadis: Society as a World of Meaning and the Anti-Speculative Stance towards History - Ktenas, Yannis (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2021)
The article aims to show that the intellectual relationship between Max Weber and Cornelius Castoriadis is far deeper and more fruitful than it has been considered so far. Starting from the exploration of Castoriadis’ own writings on the subject (most of which are available only in Greek), Yannis Ktenas claims that the strong affinity between the works of the thinkers centers around the great importance they both attribute to the concept of “meaning” in their effort to thematize the social-historical universe. An example of this importance can be found in their writings on history: they adopt a critical stance towards Hegel’s and, to some extent, Marx’s “speculative” theorization of history, counter-proposing a conception that highlights the elements of contingency and creativity of social action. Weber et Castoriadis. La société comme univers de sens et la compréhension anti-spéculative de l’histoire Cet article vise à montrer que la relation intellectuelle entre Max Weber et Cornelius Castoriadis est beaucoup plus profonde et féconde qu’elle n’a été envisagée jusqu’à maintenant. Partant de l’exploration des écrits que Castoriadis a lui-même consacré au sujet (et qui, pour la plupart, ne sont disponibles qu’en grec), Yannis Ktenas soutient que la grande affinité qui existe entre les deux penseurs réside dans l’importance majeure qu’ils attribuent au concept de « sens » pour penser l’univers social et historique. Leurs écrits sur l’histoire offrent un exemple intéressant de ce point de vue : tous deux adoptent une position critique face à la théorisation « spéculative » de l’histoire qu’a Hegel et (jusqu’à un certain point) Marx, et ils en proposent une conception qui met l’accent sur la contingence et la créativité de l’action sociale.